Yellowing-resistant vamp material and preparation method thereof
By using polyether polyols, isocyanates and chain extenders in the upper material, and adding pore-forming particles, ultraviolet absorbing particles and fill particles, the problems of yellowing and insufficient wear resistance of the upper material are solved, and the material is realized The yellowing resistance and wear resistance are improved, extending service life.
Patent Information
- Application Number
- CN202411348562.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-02-14
AI Technical Summary
Existing upper materials are prone to yellowing when facing changes in sunlight and humidity, and are not able to wear resistance and service life.
Polyurethane materials are prepared using polyether polyols, isocyanates and chain extenders, and the air permeability, UV aging resistance and wear resistance of the material are improved by adding pore-forming particles, ultraviolet absorbing particles and filler particles.
It achieves yellowing resistance and wear resistance of the upper material, extends the service life, while maintaining the softness, comfort and breathability of the material.
Smart Images

Figure BDA0005061671700000091
Abstract
Description
Technical Field
[0001] The present application relates to the field of shoe upper materials, and more specifically, to a yellowing-resistant shoe upper material and a preparation method thereof. Background Art
[0002] The leather surface of casual shoes is generally made of leather, which is generally divided into genuine leather, synthetic leather, cloth, etc.
[0003] Although genuine leather uppers are soft and comfortable, not prone to itching and discomfort, and have good air permeability, they are easily affected by environmental factors such as sunlight and humidity, causing yellowing in color and yellowing problems. They are also difficult to maintain and can easily damage the leather surface during wiping. Although cloth uppers are light, breathable, and soft, they are easily adhered to dirt, dust, and oil stains, and have poor wear resistance and elasticity, which affects the service life of the upper during wiping. Synthetic leather uppers are more environmentally friendly and have better wear resistance. They are not easily damaged during wiping, but synthetic leather uppers are prone to problems such as yellowing.
[0004] Therefore, how to prepare a new upper material so that it has the advantages of yellowing resistance and good wear resistance is a problem to be solved. Summary of the invention
[0005] In order to prepare a new upper material that has the advantages of both yellowing resistance and good wear resistance, the present application provides a yellowing-resistant upper material and a preparation method thereof.
[0006] In a first aspect, the present application provides a yellowing-resistant upper material, which adopts the following technical solution: A yellowing-resistant upper material comprises the following raw materials in parts by weight: 80-100 parts of polyether polyol, 60-80 parts of isocyanate, 10-20 parts of chain extender, 5-10 parts of pore-forming particles, 2-5 parts of ultraviolet absorbing particles, 2-10 parts of filling particles, 1-5 parts of lubricant, 1-5 parts of dispersant, 1-3 parts of antioxidant and 1-5 parts of ultraviolet absorber.
[0007] By adopting the above technical scheme, a soft and comfortable polyurethane upper material is prepared by using polyether polyol, isocyanate and chain extender. After adding pore-forming particles and ultraviolet absorbing particles, the pore-forming effect of the pore-forming particles is utilized to ensure the air permeability of the polyurethane upper material, and the pore effect of the pore-forming particles is utilized to facilitate the refraction of ultraviolet rays. The ultraviolet absorbing effect of the ultraviolet absorbing particles and the ultraviolet absorber is combined to avoid the polyurethane upper material from yellowing and affecting its service life as much as possible. The filling effect of the filling particles and the dispersant is combined to improve the wear resistance of the upper material. The lubricant is combined to facilitate demoulding and ensure the integrity of the upper material, so that the upper material has the advantages of yellowing resistance and good wear resistance.
[0008] Preferably, the pore-forming particles are made of porous microparticles loaded with ammonium bicarbonate solution, bonded with shellac solution, and finally bonded with chitosan fibers, and the mass ratio of porous microparticles, ammonium bicarbonate solution, shellac solution, and chitosan fibers is 1:1-2:0.4-0.8:0.5-1.
[0009] By adopting the above technical scheme, the porous particles utilize their better adsorption effect to absorb the ammonium bicarbonate solution, and then adhere to the shellac solution, and utilize the viscosity of the shellac solution to adhere to the chitosan fibers, so that the chitosan fibers are attached to the surface of the porous particles. After being heated during the processing, the ammonium bicarbonate solution gradually thermally decomposes and produces gas, breaking through the shellac film formed by the shellac solution on the surface of the porous particles, so that the pores of the porous particles are partially connected with the outside world. Combined with the entanglement of the chitosan fibers and the porous effect of the chitosan fibers, the air permeability of the pore-forming particles is further guaranteed, thereby ensuring the air permeability of the upper material.
[0010] However, the breathable area is in contact with oxygen, ultraviolet rays and other substances over a larger area, which makes yellowing problem more likely to occur. By utilizing the good antioxidant effect of shellac solution near the pores, combined with the spatial network pores formed by porous particles and chitosan fibers to absorb and reflect ultraviolet rays, yellowing of polyurethane near the pore-forming particles is prevented; combined with the good wear-resistant effect of porous particles, shellac and chitosan fibers, the wear resistance of the upper material is further improved.
[0011] Preferably, the porous particles are composed of sepiolite particles and silica aerogel in a mass ratio of 1:0.1-0.3.
[0012] By adopting the above technical scheme, both the sepiolite particles and the silica aerogel have multiple open pores, which are convenient for absorbing and refracting ultraviolet rays while ensuring the breathability of the upper material, so that the finished upper material has good breathability and good yellowing resistance; at the same time, the sepiolite particles have a certain wear-resistant effect, further ensuring the wear resistance of the upper material.
[0013] Sepiolite particles and silica aerogel can absorb ammonium bicarbonate solution. After being heated during the processing and molding of the upper material, the ammonium bicarbonate gradually decomposes and produces gas, ensuring the connectivity between the pores of the silica aerogel and sepiolite particles and the external environment, thereby ensuring the air permeability of the upper material.
[0014] Preferably, the chitosan fiber is made of chitosan fiber filaments and citric acid glyceride solution in a mass ratio of 1:0.2-0.5.
[0015] By adopting the above technical scheme, chitosan fiber filaments utilize their good flexibility and good adsorption effect to facilitate the adsorption of glyceryl citrate solution, and the amino and carboxyl groups on the chitosan fiber cooperate with the hydrophilic carboxyl groups in the glyceryl citrate solution to facilitate attraction and connection, while the hydrophobic groups in the glyceryl citrate solution can give the chitosan fiber a certain hydrophobic effect. The chitosan fiber is wrapped and attached to the peripheral surface of the pore-forming particles, and the partial shellac film formed by the shellac solution can give the pore-forming particles a certain hydrophobic effect, thereby ensuring that the upper material has a certain waterproof effect while having good air permeability, and is not easily affected by moisture and accelerates the yellowing of the upper material.
[0016] The chitosan fiber filaments and glycerol citrate solution define the raw material ratio, so that the amino and carboxyl groups of the chitosan fiber part on the surface of the porous particles can contact and cross-link with polyether polyols, isocyanates and other substances, thereby increasing the cross-linking density between the pore-forming particles and polyurethane, ensuring the structural density, and thus improving the wear resistance of the upper material.
[0017] Preferably, the ultraviolet absorbing particles are made of nano zinc oxide particles, hydroxyapatite particles and polycaprolactone diol solution in a mass ratio of 1:1-3:0.5-1.5.
[0018] By adopting the above technical scheme, nano zinc oxide particles, hydroxyapatite particles and polycaprolactone diol solution are matched, and the good ultraviolet absorption effect of nano zinc oxide particles is used in combination with the ultraviolet refraction of hydroxyapatite particles and the absorption of ultraviolet rays by internal pores, so as to further improve the ultraviolet aging resistance of the upper material, thereby making the upper material less prone to yellowing; the hydroxyl groups in the polycaprolactone diol solution are convenient for connecting with polyether polyols and isocyanates, thereby improving the cross-linking effect of the ultraviolet absorbing particles and polyurethane, improving the structural density of the upper material, and the good wear resistance of zinc oxide particles and hydroxyapatite particles is combined, so that the finished upper material has good ultraviolet aging resistance and wear resistance.
[0019] Preferably, the hydroxyapatite particles are porous hydroxyapatite with an average porosity of 70-80%.
[0020] By adopting the above technical solution, the porosity of the hydroxyapatite particles is limited to ensure that the ultraviolet rays reaching the upper material are absorbed and refracted, thereby reducing the aging effect of ultraviolet rays on the polyurethane material and extending the usability of the upper material.
[0021] Preferably, the filling particles are made of polycrystalline silicon, boron nitride and polyvinyl alcohol solution in a mass ratio of 1:1-2:0.5-1.
[0022] By adopting the above technical scheme, polycrystalline silicon, boron nitride and polyvinyl alcohol solution are matched, and the viscosity of the polyvinyl alcohol solution is utilized to facilitate bonding to the surface of polycrystalline silicon and boron nitride. The cross-linking effect of the hydroxyl groups in polyvinyl alcohol with polyether polyols and isocyanates is utilized to improve the bonding stability of polycrystalline silicon and boron nitride in polyurethane. Combined with the good wear resistance of polycrystalline silicon and boron nitride, the upper material has better wear resistance.
[0023] Preferably, the lubricant consists of calcium stearate and ozokerite in a mass ratio of 1:0.5-1.
[0024] By adopting the above technical solution and utilizing the lubricating effect of calcium stearate and ceresin, demoulding is facilitated while the surface smoothness can be improved.
[0025] Preferably, the ultraviolet absorber consists of ultraviolet absorber UV327 and ultraviolet absorber UV-571 in a mass ratio of 1:0.5-1.
[0026] By adopting the above technical solution, the upper material has better resistance to ultraviolet aging, thereby extending the service life of the upper material.
[0027] In a second aspect, the present application provides a method for preparing a yellowing-resistant upper material, using the following technical solution: A method for preparing a yellowing-resistant upper material, comprising the following steps: S1. Weigh polyether polyol, isocyanate, chain extender, pore-forming particles, ultraviolet absorbing particles, and filler particles, mix and stir evenly to obtain a primary mixture; S2, adding lubricant, dispersant, antioxidant and ultraviolet absorber to the primary mixture, mixing and stirring evenly to obtain a mixture; S3, reacting and molding the mixture to obtain a finished product.
[0028] By adopting the above technical solution, the obtained upper material has good ultraviolet aging resistance, good air permeability and good wear resistance.
[0029] In summary, this application has the following beneficial effects: 1. A soft and comfortable polyurethane upper material is prepared by using polyether polyol, isocyanate and chain extender. After adding pore-forming particles and ultraviolet absorbing particles, the pore-forming effect of the pore-forming particles is utilized to ensure the air permeability of the polyurethane upper material, and the pore effect of the pore-forming particles is utilized to facilitate the refraction of ultraviolet rays. The ultraviolet absorbing effect of the ultraviolet absorbing particles and the ultraviolet absorber is combined to avoid the polyurethane upper material from yellowing and affecting its service life as much as possible. The filling effect of the filling particles and the dispersant is combined to improve the wear resistance of the upper material. The lubricant is combined to facilitate demoulding and ensure the integrity of the upper material, so that the upper material has the advantages of yellowing resistance and good wear resistance.
[0030] 2. The pore-forming particles, UV-absorbing particles and ozokerite are combined. The hydrophobicity of the shellac film on the surface of the pore-forming particles, the hydrophobic effect of the citric acid glyceride solution on the surface of the chitosan fiber, the hydrophobicity of the polycaprolactone diol solution on the surface of the UV-absorbing particles and the water-proof effect of the ozokerite are used. In the upper material, it is not easy to absorb moisture and cause yellowing, whether in the pores or other positions, thereby ensuring the service life of the upper material.
[0031] 3. The combination of sepiolite particles, silica aerogel, chitosan fibers, nano zinc oxide particles, hydroxyapatite nanowires, and ultraviolet absorbers utilizes the porous effect of sepiolite particles and silica aerogel to absorb and refract ultraviolet rays, and the spatial network pores formed by chitosan fibers on the surface of the pore-forming particles further refract and absorb ultraviolet rays, thereby achieving good yellowing resistance in the breathable pores of the upper material. The good filling effect of nano zinc oxide particles, hydroxyapatite nanowires, and ultraviolet absorbers is utilized inside the upper material, and their absorption and refraction effects on ultraviolet rays are combined to control the yellowing of the upper material due to ultraviolet rays, thereby increasing the service life of the upper material. DETAILED DESCRIPTION
[0032] The present application is further described in detail below with reference to the embodiments.
[0033] Preparation example of pore-forming particles The following raw materials include glyceryl citrate, which was purchased from Hanshuer Biotechnology Co., Ltd.; other raw materials and equipment are commercially available.
[0034] Preparation Example 1: The pore-forming particles are prepared by the following method: 0.35 kg of citric acid glyceride solution was uniformly sprayed on the surface of 1 kg of chitosan fiber filaments, wherein the citric acid glyceride solution was a 2% by mass citric acid glyceride chloroform solution, and the chloroform was removed by drying to obtain chitosan fibers; the average length of the chitosan fiber filaments was 40 μm; 1 kg of sepiolite particles and 0.2 kg of silica aerogel are weighed and mixed and stirred evenly, wherein the average particle size of the sepiolite particles is 80 μm, and the average particle size of the silica aerogel is 60 μm, so as to obtain porous particles; then 1.5 kg of ammonium bicarbonate solution is added at a speed of 60 mL / min, wherein the ammonium bicarbonate solution is an ammonium bicarbonate aqueous solution with a mass fraction of 10%, during the adding process, the porous particles are continuously stirred at a speed of 1000 r / min, and the stirring is continued for 5 minutes after the adding is completed, so as to obtain loaded particles; 0.6 kg of shellac solution is uniformly sprayed on the surface of the loaded particles, wherein the shellac solution is a shellac ethanol solution with a mass fraction of 1%, and the ethanol is anhydrous ethanol; finally, 0.8 kg of chitosan fiber is added at a speed of 60 g / min, wherein the loaded particles are continuously stirred at a speed of 200 r / min during the adding process, and the finished product is obtained through drying and dispersion; and the finished product is sieved through an 80-mesh sieve.
[0035] Preparation Example 2: This preparation example differs from Preparation Example 1 in that: 0.2 kg of citric acid glyceride solution was uniformly sprayed on the surface of 1 kg of chitosan fiber to obtain chitosan fiber; the average length of the chitosan fiber was 40 μm; 1 kg of sepiolite particles and 0.1 kg of silica aerogel are weighed and mixed and stirred evenly, wherein the average particle size of the sepiolite particles is 80 μm, and the average particle size of the silica aerogel is 60 μm, so as to obtain porous particles; then 1 kg of ammonium bicarbonate solution is added at a speed of 60 mL / min, wherein the ammonium bicarbonate solution is an ammonium bicarbonate aqueous solution with a mass fraction of 10%, during the adding process, the porous particles are continuously stirred at a rotation speed of 1000 r / min, and the stirring is continued for 5 minutes after the adding is completed, so as to obtain loaded particles; 0.4 kg of shellac solution is uniformly sprayed on the surface of the loaded particles, wherein the shellac solution is a shellac ethanol solution with a mass fraction of 1%, and the ethanol is anhydrous ethanol; finally, 0.5 kg of chitosan fiber is added at a speed of 60 g / min, wherein the loaded particles are continuously stirred at a rotation speed of 200 r / min during the adding process, and the finished product is obtained through drying and dispersion; and the finished product is sieved through an 80-mesh sieve.
[0036] Preparation Example 3: This preparation example differs from Preparation Example 1 in that: 0.5 kg of citric acid glyceride solution was uniformly sprayed on the surface of 1 kg of chitosan fiber to obtain chitosan fiber; the average length of the chitosan fiber was 40 μm; 1 kg of sepiolite particles and 0.3 kg of silica aerogel are weighed and mixed and stirred evenly, wherein the average particle size of the sepiolite particles is 80 μm, and the average particle size of the silica aerogel is 60 μm, so as to obtain porous particles; then 2 kg of ammonium bicarbonate solution is added at a speed of 60 mL / min, wherein the ammonium bicarbonate solution is an ammonium bicarbonate aqueous solution with a mass fraction of 10%, during the adding process, the porous particles are continuously stirred at a speed of 1000 r / min, and the stirring is continued for 5 minutes after the adding is completed, so as to obtain loaded particles; 0.8 kg of shellac solution is uniformly sprayed on the surface of the loaded particles, wherein the shellac solution is a shellac ethanol solution with a mass fraction of 1%, and the ethanol is anhydrous ethanol; finally 1 kg of chitosan fiber is added at a speed of 60 g / min, wherein the loaded particles are continuously stirred at a speed of 200 r / min during the adding process, and the finished product is obtained through drying and dispersion; and the finished product is sieved through an 80-mesh sieve.
[0037] Preparation Example of UV Absorbing Particles The following raw materials are all commercially available.
[0038] Preparation Example 4: Ultraviolet absorbing particles are prepared by the following method: 1 kg of nano zinc oxide particles and 2 kg of hydroxyapatite particles are weighed and mixed and stirred evenly, wherein the average particle size of the nano zinc oxide particles is 200 nm, the average particle size of the hydroxyapatite particles is 10 μm, and the hydroxyapatite is porous hydroxyapatite with an average porosity of 75%. Then, 1 kg of polycaprolactone diol solution is evenly sprayed, wherein the mass fraction of the polycaprolactone diol solution is 1%, the molecular weight of the polycaprolactone diol is 20,000, and the solvent is ethyl acetate. After drying and dispersing until the nano zinc oxide particles and the hydroxyapatite particles do not stick to each other and agglomerate, a finished product is obtained.
[0039] Preparation Example 5: This preparation example differs from Preparation Example 4 in that: 1 kg of nano zinc oxide particles and 1 kg of hydroxyapatite particles are weighed and mixed and stirred evenly, wherein the average particle size of the nano zinc oxide particles is 200 nm, the average particle size of the hydroxyapatite particles is 10 μm, and the hydroxyapatite is porous hydroxyapatite with an average porosity of 70%. Then, 0.5 kg of polycaprolactone diol solution is evenly sprayed, wherein the mass fraction of the polycaprolactone diol solution is 1%, the molecular weight of the polycaprolactone diol is 20,000, and the solvent is ethyl acetate. After drying and dispersing until the nano zinc oxide particles and the hydroxyapatite particles do not stick to each other and agglomerate, a finished product is obtained.
[0040] Preparation Example 6: This preparation example differs from Preparation Example 4 in that: 1 kg of nano zinc oxide particles and 3 kg of hydroxyapatite particles are weighed and mixed and stirred evenly, wherein the average particle size of the nano zinc oxide particles is 200 nm, the average particle size of the hydroxyapatite particles is 10 μm, and the hydroxyapatite is porous hydroxyapatite with an average porosity of 80%. Then, 1.5 kg of polycaprolactone diol solution is evenly sprayed, wherein the mass fraction of the polycaprolactone diol solution is 1%, the molecular weight of the polycaprolactone diol is 20,000, and the solvent is ethyl acetate. After drying and dispersing until the nano zinc oxide particles and the hydroxyapatite particles do not stick to each other and agglomerate, a finished product is obtained.
[0041] Preparation example of filled particles The following raw materials are all commercially available.
[0042] Preparation Example 7: Filling particles are prepared by the following method: 0.8 kg of polyvinyl alcohol solution is evenly sprayed on the surface of 1 kg of polycrystalline silicon and 1.5 kg of boron nitride. The average particle size of the polycrystalline silicon is 20 μm, the average particle size of the boron nitride is 20 μm, and the polyvinyl alcohol solution is a polyvinyl alcohol aqueous solution with a mass fraction of 1%. The product is obtained by drying and dispersing until the polycrystalline silicon and the boron nitride do not stick to each other and agglomerate.
[0043] Preparation Example 8: This preparation example differs from Preparation Example 7 in that: 0.5 kg of polyvinyl alcohol solution is evenly sprayed on the surface of 1 kg of polycrystalline silicon and 1 kg of boron nitride, and the solution is dried and dispersed until the polycrystalline silicon and the boron nitride do not stick to each other and agglomerate to obtain a finished product.
[0044] Preparation Example 9: This preparation example differs from Preparation Example 7 in that: 1 kg of polyvinyl alcohol solution is evenly sprayed on the surface of 1 kg of polycrystalline silicon and 2 kg of boron nitride, and the solution is dried and dispersed until the polycrystalline silicon and the boron nitride do not stick to each other and agglomerate to obtain a finished product. Example
[0045] Among the following raw materials, polyether polyol was purchased from Shandong Huibang New Material Technology Co., Ltd.; isocyanate was purchased from hexamethylene diisocyanate of Jinan Hongwang Chemical Co., Ltd.; other raw materials were all commercially available.
[0046] Embodiment 1: A yellowing-resistant upper material: 90kg of polyether polyol, 70kg of isocyanate, 15kg of chain extender, 8kg of pore-forming particles, 4kg of ultraviolet absorbing particles, 6kg of filling particles, 3kg of lubricant, 3kg of dispersant, 2kg of antioxidant, and 3kg of ultraviolet absorber; the chain extender is propylene glycol; the pore-forming particles are selected from the pore-forming particles prepared in Preparation Example 1, the ultraviolet absorbing particles are selected from the ultraviolet absorbing particles prepared in Preparation Example 4, and the filling particles are selected from the filling particles prepared in Preparation Example 7; the lubricant is composed of calcium stearate and ozokerite in a mass ratio of 1:1; the dispersant is polyethylene glycol 800; the antioxidant is antioxidant 1010; the ultraviolet absorber is composed of ultraviolet absorber UV327 and ultraviolet absorber UV-571 in a mass ratio of 1:1; The preparation method is as follows: S1. Weigh the polyurethane prepolymer, isocyanate, pore-forming particles, ultraviolet absorbing particles, and filling particles, mix and stir evenly to obtain a primary mixture; S2. Add lubricant, dispersant, antioxidant and ultraviolet absorber to the primary mixture, mix and stir evenly to obtain a mixture; S3. Stir and react the mixture at 90° C. for 30 minutes, then at 50° C. for 30 minutes, and finally form and demold the mixture in a mold to obtain a finished product.
[0047] Embodiment 2: This embodiment differs from Embodiment 1 in that: 80kg of polyether polyol, 60kg of isocyanate, 10kg of chain extender, 5kg of pore-forming particles, 2kg of ultraviolet absorbing particles, 2kg of filling particles, 1kg of lubricant, 1kg of dispersant, 1kg of antioxidant, and 1kg of ultraviolet absorber; the chain extender is propylene glycol; the pore-forming particles are selected from the pore-forming particles prepared in Preparation Example 2, the ultraviolet absorbing particles are selected from the ultraviolet absorbing particles prepared in Preparation Example 5, and the filling particles are selected from the filling particles prepared in Preparation Example 8; the lubricant is composed of calcium stearate and ozokerite in a mass ratio of 1:0.5; the dispersant is polyethylene glycol 800; the antioxidant is antioxidant 1010; the ultraviolet absorber is composed of ultraviolet absorber UV327 and ultraviolet absorber UV-571 in a mass ratio of 1:0.5.
[0048] Embodiment 3: This embodiment differs from Embodiment 1 in that: 100kg of polyether polyol, 80kg of isocyanate, 20kg of chain extender, 10kg of pore-forming particles, 5kg of ultraviolet absorbing particles, 10kg of filling particles, 5kg of lubricant, 5kg of dispersant, 3kg of antioxidant, and 5kg of ultraviolet absorber; the chain extender is propylene glycol; the pore-forming particles are selected from the pore-forming particles prepared in Preparation Example 3, the ultraviolet absorbing particles are selected from the ultraviolet absorbing particles prepared in Preparation Example 6, and the filling particles are selected from the filling particles prepared in Preparation Example 9; the lubricant is composed of calcium stearate and ozokerite in a mass ratio of 1:1; the dispersant is polyethylene glycol 800; the antioxidant is antioxidant 1010; the ultraviolet absorber is composed of ultraviolet absorber UV327 and ultraviolet absorber UV-571 in a mass ratio of 1:1.
[0049] Embodiment 4: This embodiment differs from Embodiment 1 in that: During the preparation of the pore-forming particles, the shellac solution is replaced by an equal mass of sodium alginate solution, wherein the sodium alginate solution is a sodium alginate aqueous solution with a mass fraction of 1%.
[0050] Embodiment 5: This embodiment differs from Embodiment 1 in that: During the preparation of the pore-forming particles, chitosan fibers are replaced by chitosan fiber filaments of equal mass, that is, there is no glycerol citrate solution on the surface of the chitosan fibers.
[0051] Embodiment 6: This embodiment differs from Embodiment 1 in that: During the preparation of the pore-forming particles, the silica aerogel was replaced with an equal mass of silica, and the average porosity of the silica was 5%.
[0052] Embodiment 7: This embodiment differs from Embodiment 1 in that: The polycaprolactone diol solution was not added to the ultraviolet absorbing particles.
[0053] Embodiment 8: This embodiment differs from Embodiment 1 in that: No polyvinyl alcohol solution was added to the filling particles.
[0054] Comparative Example Comparative Example 1: The difference between this comparative example and Example 1 is that: No pore-forming particles, UV-absorbing particles, or filler particles are added to the raw materials.
[0055] Performance testing 1. Air permeability test The upper materials were prepared by the preparation methods of Examples 1-3, 6 and Comparative Example 1, respectively, and the air permeability was tested with reference to QB / T 2799-2006, and the data were recorded.
[0056] 2. Yellowing resistance test The upper materials were prepared by the preparation methods of Examples 1-8 and Comparative Example 1, respectively. The upper materials were treated with a UVA-340 40W aging test lamp. After irradiation with ultraviolet rays for 3 days, the yellowing area of the upper material per unit area was observed and calculated. The yellowing area was the total area from mild yellowing to severe yellowing, and the data was recorded.
[0057] 3. Wear resistance test The upper material was prepared by the preparation methods of Examples 1-8 and Comparative Example 1 respectively, and was polished 2000 times by GT-7012-T, No. 22 grinding wheel, weight load 1KG, and the wear mass and data were recorded.
[0058] 4. Waterproof test The upper materials were prepared by the preparation methods of Examples 1-8 and Comparative Example 1, and the tensile strength of the upper materials was tested by a tensile testing machine to obtain the initial tensile strength. The upper materials were placed under the conditions of relative humidity of 95% and ambient temperature of 40°C for 3 days, and the tensile strength was tested again to obtain the wet-treated tensile strength. The tensile strength difference = initial tensile strength - wet-treated tensile strength was recorded, and the data was recorded.
[0059] Table 1 Performance test table (the " / " in the following table indicates that the corresponding embodiment or comparative example did not test the item, so there is no data) It can be seen from Examples 1-3 and Table 1 that the upper material prepared in the present application has good air permeability, good yellowing resistance, good wear resistance, certain waterproof and moisture-proof effects in humid environments, and can extend the service life of the upper material.
[0060] Combining Example 1 and Examples 4-8 and Table 1, it can be seen that in the preparation process of the pore-forming particles in Example 4, the shellac solution is replaced with an equal mass of sodium alginate solution. Compared with Example 1, the yellowing area and the wear mass of the upper material prepared in Example 4 are greater than those in Example 1, and the difference in tensile strength is greater than that in Example 1; this shows that although the sodium alginate solution can also form a coating, it has poor waterproof and moisture-proof properties, is easily soluble in water, and causes the porous particles to absorb water, affecting the waterproof and moisture-proof properties, and shellac has a certain strength and good UV resistance, which can improve the yellowing resistance and wear resistance of the upper material.
[0061] In the preparation process of the pore-forming particles in Example 5, chitosan fibers are replaced with chitosan fiber filaments of equal mass, that is, there is no citrate glyceride solution on the surface of the chitosan fibers. Compared with Example 1, the yellowing area and abrasion mass of the upper material prepared in Example 5 are greater than those in Example 1, and the difference in tensile strength is greater than that in Example 1; this indicates that the carboxyl group of the citrate glyceride solution is utilized on the surface of the chitosan fibers to facilitate adhesion to the surface of the chitosan fibers, thereby improving the yellowing resistance effect, and can also improve the wear resistance, and can also block moisture and humidity in the external environment, thereby improving the service life of the upper material.
[0062] In the preparation process of the pore-forming particles in Example 6, the silica aerogel is replaced by the same mass of silica. Compared with Example 1, the air permeability of the upper material prepared in Example 6 is lower than that in Example 1, and the yellowing area is smaller; this indicates that the porosity of silica is lower than that of silica aerogel. Silica aerogel has a multi-open pore structure, which can improve the air permeability; and the porous structure of silica aerogel can reflect and refract ultraviolet rays in multiple directions, and the pores can also absorb ultraviolet rays, thereby improving the resistance to ultraviolet radiation and improving the yellowing resistance of the finished upper material.
[0063] No polycaprolactone diol solution was added to the ultraviolet absorbing particles in Example 7. Compared with Example 1, the yellowing area and abrasion mass of the upper material prepared in Example 7 were greater than those in Example 1, and the difference in tensile strength was greater than that in Example 1. This indicates that polycaprolactone diol is hydrophobic and can block moisture and humid gas, thereby improving the waterproof and moisture-proof properties of the upper material and improving the wear resistance.
[0064] No polyvinyl alcohol solution was added to the filling particles in Example 8. Compared with Example 1, the yellowing area and abrasion mass of the upper material prepared in Example 8 were greater than those in Example 1, and the difference in tensile strength was greater than that in Example 1. This indicates that polyvinyl alcohol can improve the cross-linking effect of filling particles with materials such as polyether polyols and improve the structural density, thereby improving wear resistance and UV resistance.
[0065] From Example 1 and Comparative Example 1 and Table 1, it can be seen that no pore-forming particles, ultraviolet absorbing particles and filling particles are added to the raw materials of Comparative Example 1. Compared with Example 1, the yellowing area and abrasion mass of the upper material prepared in Comparative Example 1 are greater than those in Example 1, and the difference in tensile strength is greater than that in Example 1; this indicates that the pore-forming particles can improve the air permeability, the ultraviolet absorbing particles can improve the yellowing resistance, and the filling particles can improve the wear resistance.
[0066] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A yellowing-resistant upper material, characterized in that: The invention comprises the following raw materials in parts by weight: 80-100 parts of polyether polyol, 60-80 parts of isocyanate, 10-20 parts of chain extender, 5-10 parts of pore-forming particles, 2-5 parts of ultraviolet absorbing particles, 2-10 parts of filling particles, 1-5 parts of lubricant, 1-5 parts of dispersant, 1-3 parts of antioxidant and 1-5 parts of ultraviolet absorber.
2. The yellowing-resistant upper material according to claim 1, characterized in that: The pore-forming particles are made of porous microparticles loaded with ammonium bicarbonate solution, bonded with shellac solution, and finally bonded with chitosan fibers. The mass ratio of the porous microparticles, the ammonium bicarbonate solution, the shellac solution, and the chitosan fibers is 1:1-2:0.4-0.8:0.5-1.
3. The yellowing-resistant upper material according to claim 2, characterized in that: The porous particles are composed of sepiolite particles and silicon dioxide aerogel in a mass ratio of 1:0.1-0.
3.
4. The yellowing-resistant upper material according to claim 2, characterized in that: The chitosan fiber is made of chitosan fiber filaments and citric acid glyceride solution in a mass ratio of 1:0.2-0.
5.
5. The yellowing-resistant upper material according to claim 1, characterized in that: The ultraviolet absorption particles are made of nano zinc oxide particles, hydroxyapatite particles and polycaprolactone diol solution in a mass ratio of 1:1-3:0.5-1.
5.
6. The yellowing-resistant upper material according to claim 5, characterized in that: The hydroxyapatite particles are porous hydroxyapatite with an average porosity of 70-80%.
7. The yellowing-resistant upper material according to claim 1, characterized in that: The filling particles are made of polysilicon, boron nitride and polyvinyl alcohol solution in a mass ratio of 1:1-2:0.5-1.
8. The yellowing-resistant upper material according to claim 1, characterized in that: The lubricant consists of calcium stearate and ozokerite in a mass ratio of 1:0.5-1.
9. The yellowing-resistant upper material according to claim 1, characterized in that: The ultraviolet absorber is composed of ultraviolet absorber UV327 and ultraviolet absorber UV-571 in a mass ratio of 1:0.5-1.
10. The method for preparing a yellowing-resistant upper material according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Weigh polyether polyol, isocyanate, chain extender, pore-forming particles, ultraviolet absorbing particles, and filler particles, mix and stir evenly to obtain a primary mixture; S2, adding a lubricant, a dispersant, an antioxidant and an ultraviolet absorber to the primary mixture, mixing and stirring to obtain a mixture; S3, the mixture is reacted and formed to obtain a finished product.